Flood risk and shelter suitability mapping using geospatial technique for sustainable urban flood management: a case study in Palembang city, South Sumatera, Indonesia - Muhammad Rendana; Wan Mohd Razi Idris; Sahibin Abdul Rahim; Hazem Ghassan Abdo; Hussein Almohamad; Ahmed Abdullah Al Dughairi (Geology, Ecology, and Landscapes)
The populous city of Palembang is one of the most flood-prone cities in the Indonesian region. After some decades, the magnitude, duration, and frequency of floods have increased. Thus, this study aimed to develop flood risk and flood shelter suitability maps using the Analytic Hierarchy Process (AHP) and Geographical Information System (GIS) integration. Several flood-related factors that used in this study such as elevation, population, slope, land cover, distance from a river, drainage density, distance to a road, distance to a settlement, and soil type. Results found that the flood risk map of the study area was divided into three classes; 30.3% of the area was at high flood risk, while 60.5% was at moderate risk, and 9.2% of the area was at low flood risk. Moreover, flood shelter suitability assessments revealed that approximately 4.1% of flood shelters were highly suitable, 19.4% were moderately suitable, 60.5% were lowly suitable, and 16.1% were very lowly suitable. The highest suitability areas were predominantly found on the northwest and north sides of study area which were higher in elevation (ranging 13–41 m) and farther from the river. They could be assumed to be good choices for flood shelters.